Perceptions of Educators, Accounting Students and Accountants Public Accountant against Ethics of Financial Statement Preparation (Studies at University and KAP in Semarang) - Imam Prayogo; Teuku Afrizal (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to examine differences in perceptions between teaching accountants, accounting students, and accountants on the ethics of preparing financial statements. Ethical indicators for the preparation of financial statements are represented in earnings management, misstatements, disclosures, cost-benefits, and responsibilities. This research was conducted at universities and public accounting firms in Semarang. This research was conducted with a survey method of 70 respondents from teaching accountants, 75 accounting students, and 40 accountants respondents at universities and public accounting firms in Semarang. As an analysis tool, ANOVA is used for hypotheses H1, H2, H3, and H4. Before testing the hypothesis, first the validity and reliability tests are carried out for all the questionnaires that have been collected. Validity and reliability tests show that all data are valid and reliable. Then the questionnaire was tested by ANOVA and strengthened by the Independent Sample T Test. Anova results show that there are differences in perceptions between teaching accountants, accounting students and accountants. However, there was no difference in perceptions between teaching accountants and accountants. Therefore it can be concluded that there are differences in perceptions between teaching accountants, accounting students, and accountants on the ethics of preparing financial statements.